Effect of Transition Planning on Postsecondary Support Receipt by Students With Disabilities. (July 2016) - Newman, Lynn A.; Madaus, Joseph W.; Javitz, Harold S.
The authors of this article analyzed data from the National Longitudinal Transition Study-2 to determine the effect of receiving transition planning education and having a transition plan that specified needed postsecondary accommodations on the receipt of disability-specific services and generally available supports at the postsecondary level by students with disabilities. Propensity model analyses indicated that both variables significantly increased the odds that students with disabilities would receive disability-specific and generally available supports at 2-year institutions. In addition, students with transition plans specifying accommodations were more likely to receive disability-related supports at career and technical education (CTE) schools, and CTE students who had received transition planning education in high school were more likely to receive generally available supports. The results provide important implications for policy and practice, and a strong foundation for further exploration of the linkages between transition planning experiences and receipt of disability-specific and generally available supports at postsecondary schools.